К вопросу о языковом и речевом cтатусе так называемых “сложносоставных слов” - Неделяева-Степонавичене, С. И. (Kalbotyra, 1987)
The article deals with the structures which in Slavonic and Baltic linguistics are traditionally called by different terms as “appositional compounds”, “binoms”, “twins”, “additional word groups”, “appositional word groups”, etc. An attempt has been made to show that they are neither word groups nor compounds. They are structures of an inter-level, having a status of their own.